Cooling Down Local Responses to Global Climate Change - Hoffman, Susanna M.; Eriksen, Thomas Hylland; Mendes, Paulo (Berghahn Books, 2022)
Climate change is a slowly advancing crisis sweeping over the planet and affecting different habitats in strikingly diverse ways. While nations have signed treaties and implemented policies, most actual climate change assessments, adaptations, and countermeasures take place at the local level. People are responding by adjusting their practices, livelihoods, and cultures, protesting and migrating. This book portrays the diversity of explanations and remedies as expressed at the community level and its emphasis on the crucial importance of ethnographic detail in demonstrating how people in different parts of the world are scaling down the phenomenon of global warming.